Wipe it off: A meta-analytic review of the psychological consequences and antecedents of physical cleansing - Lee, Spike W S; Chen, Kathleen; Ma, Cecilia; Hoang, Joe (Psychological bulletin, 2024)
Physical cleansing is a human universal. It serves health and survival functions. It also carries rich psychological meanings that interest scholars across disciplines. What psychological effects result from cleansing? What psychological states trigger cleansing? The present meta-analysis takes stock of all experimental studies examining the psychological consequences and antecedents of cleansing-related thoughts, feelings, and behaviors (e.g., feeling less guilty after cleansing; spontaneously cleansing oneself after thinking of unwelcomed sexual encounter). It includes 129 records, 230 experiments, and 551 effects from 42,793 participants. Effect sizes were synthesized in random-effects models using robust variance estimates with small-sample corrections, supplemented by other techniques. Outliers were excluded using leave-one-out diagnostics and sensitivity analysis. Publication bias was assessed and corrected for using eight methods. Theoretical, methodological, sample, and report moderators were coded. After excluding outliers, without bias correction, the synthesized effect size estimate was = 0.315, 95% CI [0.277, 0.354]. Using various bias correction methods, the estimate ranged from = 0.103 to 0.331 and always exhibited considerable heterogeneity. Effect sizes were especially large for behavioral measures and varied significantly between sample types, sample regions, and report types. Meanwhile, effects were domain-general (observed in the moral domain and beyond), bidirectional (physical cleansing ↔ psychological variables), and robust across theoretical types, manipulation operationalizations, and study designs. Limitations included mixed replicability, suboptimal methodological rigor, and restricted sample diversity. We recommend future studies to (a) incorporate power analysis, preregistration, and replication; (b) investigate generalizability across samples; (c) strengthen discriminant validity; and (d) test competing theoretical accounts. (PsycInfo Database Record (c) 2024 APA, all rights reserved).